Treatment of Whole-Plant Corn Silage With Lactic Acid Bacteria and Organic Acid Enhances Quality by Elevating Acid Content, Reducing pH, and Inhibiting Undesirable Microorganisms - Jiang, Fu-gui; Cheng, Hai-jian; Liu, Dong; Wei, Chen; An, Wen-juan; Wang, Ya-fang; Sun, Hai-tao; Song, En-liang (Frontiers in Microbiology, 2020)
We investigated the variation in microbial community and fermentation characteristics of whole-plant corn silage after treatment with lactic acid bacteria (LAB) and organic acids. The fresh corn forages were treated with a combination of L. acidophilus and L. plantarum (106 CFU/g fresh material) or a 7:1:2 ratio of formic acid, acetic acid, and propionic acid (6 mL/g fresh material) followed by 45 or 90 days of ensiling. Silages treated with LAB showed increased lactic acid content and decreased pH after 45 days. Although treatment with LAB or organic acids decreased the common and unique operational taxonomic units, indicating a reduction in microbial diversity, the relative abundance of Lactobacillus was elevated after 45 and 90 days compared with control, which was more distinct in the organic acid groups. Moreover, we found higher levels of acetic acid and increased abundance of Acetobacter in silages treated with organic acids whereas undesirable microorganisms such as Klebsiella, Paenibacillus, and Enterobacter were reduced. In summary, the quality of corn silages was improved by LAB or organic acid treatment in which LAB more effectively enhanced lactic acid content and reduced pH while organic acid inhibited the growth of undesirable microorganisms.